Development of microparticles containing polylactic acid/Bioactive glass/Caffeic acid for bone tissue engineering - Tag, Beyda; Nouri, Sabereh; Ayran, Musa; Tiryaki, Aysegul; Ulag, Songul; Dalbayrak, Basak; Yuka, Selcen Ari; Arisan, Elif Damla; Ekren, Nazmi; Ustundag, Cem Bulent; Gunduz, Oguzhan (SPRINGER, 2025)
Bone defects from trauma, fractures, infections, or neoplasms present a significant challenge, driving the need for advanced bone tissue engineering methods. This study combines caffeic acid and bioactive glass in a microparticle system to enhance their synergistic effects and boost bone regeneration by leveraging's role in cell proliferation and differentiation and osteoconductive properties of bioactive glass. Within the scope of the study, microparticles were produced via electrospray method for four different formulations: 3% polylactic acid, 3% PLA/0.1% bioactive glass, 3% PLA/0.1% caffeic acid, and 3% PLA/0.1% bioactive glass /0.1% caffeic acid. Structural characterizations of microparticles were assessed using SEM, FTIR, DSC, and XRD, while caffeic acid release profiles and biocompatibility with hFOB cells were also evaluated. Structural analyses showed that the average diameter of solely PLA microparticles of 3,54 mu m +/- 0.58 mu m could be increased up to 4.33 mu m with bioactive glass and caffeic acid. Thermal analysis indicated that bioactive glass and caffeic acid had a minimal impact on thermal properties, and in vitro tests showed bioactive glass extended caffeic acid release time by up to four times. Biocompatibility tests confirmed no cytotoxicity to hFOB cells, highlighting the potential of Polylactic acid/Bioactive glass/Caffeic acid microparticles for improving bone regeneration.
Keywords: Bioactive glass; Bone defects; Caffeic acid, electrospray; Microparticle; Polylactic acid; BIOACTIVE GLASS NANOPARTICLES; CAFFEIC ACID; DRUG-DELIVERY; INVOLVEMENT; POLYMERS; MICRO; Polymer Science